CD38+ CD45RB(low) CD4+ T cells: a population of T cells with immune regulatory activities in vitro. - Read, S; Mauze, S; Asseman, C; Bean, A; Coffman, R; Powrie, F (1998)
An antibody reactive with CD38 revealed both phenotypic and functional heterogeneity amongst CD45RB(low) cells. Functional analysis of the CD38+ and CD38- fractions showed that the latter contained T cells which responded to recall antigens and produced high levels of cytokine in response to polyclonal stimulation. In contrast, the CD38+ population failed to proliferate or to produce detectable levels of cytokines. Despite appearing unresponsive, the CD38+ population significantly inhibited anti-CD3-induced proliferation and cytokine secretion by the reciprocal CD38- population. Immune suppression required stimulation through the TCR and was dependent on a physical interaction between regulatory and responding CD4+ populations. It did not involve killing of the responding T cells or secretion of IL-10 or TGF-beta. Despite some similarities there is no direct correlation between the in vitro suppression characteristic of the CD38+ CD45RB(low) subset and in vivo suppression which has been shown to be mediated by unseparated CD45RB(low) CD4+ T cells. However, these results demonstrate that two functionally distinct subsets of T cells reside within the antigen-exposed or CD45RB(low) CD4+ T cell population and are thus generated in vivo: (1) conventional memory T cells which proliferate and secrete cytokines in response to activation and (2) a population of regulatory T cells which inhibit T cell activation in vitro. Antibodies reactive with CD38 may provide a useful tool with which to study the role of these T cell subsets in the induction and regulation of the immune response.